2021
DOI: 10.1037/cpb0000218
|View full text |Cite
|
Sign up to set email alerts
|

Building resilience resources during organizational change: A longitudinal quasi-experimental field study.

Abstract: The aim of the current quasi-experimental field study was to investigate the immediate and 3-month follow-up effects of the resilience-building program ResilienceWise, using a 2 (group) 3 3 (time) mixed design. This blended program consisted of an individual assessment, four one-on-one sessions, and two modules in the online, selfhelp, psychological fitness program Psyfit (Bolier et al., 2013). The aim was to enhance resilience resources and positive adaptation in health-care office workers (n = 91) of a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Roy et al (2019) showed that resilience moderated the negative effects of work-related stress and MWB in healthcare workers impacted by organizational reforms. Employees in organizations undergoing change also recovered significantly from the stress caused by change events after resilience-enhancement programs were introduced to effectively build resilience resources in employees (IJntema et al, 2021). Furthermore, a study by Nery et al (2020) demonstrated the possibility that the subjective risk of organizational change does not negatively predict employee well-being as employees are able to utilize alternative psychological capital, such as resilience, to sustain a positive perception of the future despite changes.…”
Section: Resilience In Response To Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Roy et al (2019) showed that resilience moderated the negative effects of work-related stress and MWB in healthcare workers impacted by organizational reforms. Employees in organizations undergoing change also recovered significantly from the stress caused by change events after resilience-enhancement programs were introduced to effectively build resilience resources in employees (IJntema et al, 2021). Furthermore, a study by Nery et al (2020) demonstrated the possibility that the subjective risk of organizational change does not negatively predict employee well-being as employees are able to utilize alternative psychological capital, such as resilience, to sustain a positive perception of the future despite changes.…”
Section: Resilience In Response To Covid-19mentioning
confidence: 99%
“…(2019) showed that resilience moderated the negative effects of work-related stress and MWB in healthcare workers impacted by organizational reforms. Employees in organizations undergoing change also recovered significantly from the stress caused by change events after resilience-enhancement programs were introduced to effectively build resilience resources in employees (IJntema et al ., 2021). Furthermore, a study by Nery et al.…”
Section: Organizational Change In Response To Covid-19mentioning
confidence: 99%